Law Enforcement of Forest Protection by Forest Police of Tellu Limpoe Resort, Cenrana Forest Management Unit, Bone Regency - Andi Alif Rama Tadampali; Hardianto Djanggih; Andi Tenri Sapada (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to examine in depth the law enforcement efforts carried out by the Forest Police in the Tellu Limpoe Resort, Cenrana Forest Management Unit, Bone Regency, and to analyze the factors that influence the effectiveness of these efforts. The research method used was an empirical approach by examining the reality in the field through interviews, observations, and official data studies. The research location was chosen because of the high rate of forest destruction, which indicates the urgency of strengthening forestry law enforcement. The results of the study show that the Forest Police carry out a number of important efforts, including patrolling forest areas, checking documents related to the distribution of forest products, receiving reports of violations, collecting information and evidence, and making temporary arrests in cases of caught in the act. These efforts contribute significantly to preventing and combating forestry crimes. To overcome the various obstacles that exist, it is necessary to increase human resource capacity, provide adequate facilities and infrastructure, and procure special Civil Servant Investigators (PPNS) in the forestry sector to strengthen the investigation process of forestry crimes, especially illegal logging, so that forest protection can be carried out optimally and sustainably.